PENGARUH PENGGUNAAN SILASE RUMPUT GAJAH YANG DIBERI SINGKONG TERHADAP KONSENTRASI VFA DAN N-NH3 CAIRAN RUMEN SAPI SECARA IN VITRO - Fitriyanto, Rifqi; Suhartati, Fransisca Maria; Rahayu, Sri (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. This study was aimed to examine the effect of using elephant grass silage fed with cassava on the concentration of VFA N-NH3 which was carried out from 7 June to 7 July at the Laboratory of Animal Nutrition and Food Science, Faculty of Animal Husbandry, Universitas Jenderal Soedirman Purwokerto. Materials and methods The materials used in this study were rumen fluid from three beef cattles taken from the slaughterhouse of Bantarwuni Village, Kembaran District, Banyumas Regency immediately after the cattle were slaughtered, silage of elephant grass, cassava, and a set of in vitro tools. The study was carried out using in vitro methods and using a randomized design (CRD) with 4 complete treatments. Each treatment was repeated 5 times. The treatments tested were R1 = 100% DM of elephant grass silage; R2 = 95% DM of elephant grass silage + 5% DM of cassava; R3= 90% DM of elephant grass silage + 10% DM of cassava; R4 = 85% DM of elephant grass silage + 15% DM of cassava. The variables measured were the concentration of VFA and N-NH3. The data obtained were analyzed for variance and if the treatment had an effect on the measured variables, it was continued with the Honestly Significant Difference (HSD) test. Results. The average concentration of VFA is R1 : 122 mM, R2 : 126 mM, R3 : 128 mM, R4 : 130 mM, while the average concentration of N-NH3 is R1 : 2.4 mM, R2 : 3.4 mM, R3 : 4 mM, R4 : 3 mM. The results of the analysis of variance shows that the use of elephant grass silage fed with cassava had no significant effect (P>0.05) on the concentration of VFA but has a very significant effect (P<0.01) on the concentration of N-NH3. The highest VFA concentration is achieved by rumen fluid which obtained 85% silage of elephant grass and 15% cassava, although statistically there is no difference. Conclusion. The average concentration of N-NH3 is still low, but the highest concentration is achieved by rumen fluid added with 90% elephant grass silage and 10% cassava.